Antenna design for solid material characterization - Abdullah Aqlan, Ahmed Abdulbaset (2022)
In this project design solid antenna are designed that are suitable for with MUT application with enhanced bandwidth. The proposed antenna was designed in CST studio software. To begin the design, a suitable substrate was chosen for the antenna. In this project, FR-4 is chosen as a substrate for the simulation. This is because the substrate has a good dielectric constant, which is good for to maintain the antenna impedance. The dielectric constant of the substrate is ε